"Holy baptism" : a reconsideration of the doctrine of holy baptism in the light of recent research - Moore, Robert Humphrey (Rhodes University, Faculty of Divinity, Department of Divinity, 1974)
Conclusion: This study has helped us to perceive the significance of Christian Baptism as it arose from its antecedents, and yet differed decisively from them in meaning and significance. We have seen how Baptism grew from the New Testament situation into the life of the Early Church. We have considered the sacramental nature of Baptism, that here, while the Community is visibly active, in this holy sacrament, God is the doer of what is done. It is by Him, whose Grace is seen in Jesus Christ, that we are brought to new life within the Community of His Covenant and what He can do for adults, He can do for infants as well. However, it is good for us to remember that His presence is also for our judgement, and that there therefore remains upon us as individuals and as Community the requirement of faith and faithfulness. We have seen how it is that the Holy Spirit is given in Baptism, and we believe it is through His indwelling presence and power that we are able to come into the Family of God and enjoy that fellowship with Him, which is salvation. We have also seen that, despite many centuries of thought and study, no final doctrinal definition of Baptism is yet achieved, and that the Churches are still giving this serious attention.
Keywords: Baptism in the Holy Spirit; Holy Spirit -- Biblical teaching